Geophysical investigation of transmissibility and hydrogeological properties of aquifer system: A case study of Edem, Eastern Nigeria - Emmanuel T. Omeje; Johnson C. Ibuot; Desmond O. Ugbor; Daniel N. Obiora (Water Supply, 2022)
This research study aimed at investigating the transmissibility magnitude of hydrogeologic units of Edem employing a vertical electrical sounding technique. This was as a result of the rapid increase in population and failures of water scheme projects in Edem. Hydraulic properties used in characterizing the transmissibility magnitude were calculated from values of aquifer resistivity and thickness. Results from the field data showed that the aquifer resistivity ranged from 34.800 to 67,561.200 Ωm while thickness ranged from 24.800 to 147.600 m. Fractional porosity with an average value of 0.290 ranged from 0.256 to 0.326. Values of surface area per unit pore volume and permeability range from 460.250 to 13,038.710 m−1 and 1.680E-09 to 1.973E-06 μm2 respectively. Hydraulic capillary radius ranges from 7.67 × 10−5 to 0.00217 m, while transmissivity values range from 0.8607 to 458.0727 m2/day. From the contour map, hydrogeologic units across the western and eastern parts of the area were depicted as having high indices of transmissibility magnitude. The northwestern part was characterized with very low indices of transmissibility. Plots of permeability against these hydraulic properties revealed their various coefficient of determination. The results from this study will assist in characterizing the hydrogeologic units of the area for proper groundwater exploration and management. HIGHLIGHTS The electrical resistivity method was employed.; Hydraulic properties were calculated from aquifer resistivity and thickness.; Groundwater transmissibility magnitude was analyzed using hydraulic properties.; Eight VES points were delineated as having high transmissibility magnitude.; Transmissibility magnitude distribution was revealed with the aid of contour maps.;